Cocriação de valor e mudança comportamental voluntária para o uso de preservativo: contribuições da lógica dominada por serviço ao marketing social - Agnaldo Keiti Higuchi (2017)
This study analyses the co-creation process, from the Service-Dominant Logic (VARGO; LUSCH, 2006) point of view, in a Social Marketing phenomena. The use of traditional commercial marketing tools in social marketing situations limits the effectiveness of social changes in terms of cognition, attitude, action and behavior. Social risks, such as the possibility of becoming infected with sexually transmitted diseases and unwanted pregnancy, would not be properly prevented. Grounded on the Service-Dominant Logic, this study aims to propose new perspectives to Social Marketing. After theoretic analysis in the literature, a conceptual model was designed to support the research on value co-creation processes in service meetings, in which the exchange includes an idea and a voluntary behavioral change to safe sex. The model shows the relationships among: (i) personality traits involved in condom frequent users value co-creation, (ii) barriers to use of condoms, and (iii) strategies leading to social change, according to beneficiaries attitudinal response. The proposed model is based on Mowen (2000) Meta-theoretic Model of Motivation and Personality, using Structural Equation Modeling to analyze the collected data. The survey empirical tests, applied to UFVJM students, revealed the personal traits openness to experience, agreeableness, need for material resources, need for information and number of interactions as predictors of attitude response. The barriers to use detected were: condom as a symbol of sexual pleasure reduction and inconvenience, presence of reliable single partner and unpredictability of casual sex. This study suggests four strategic aims to social behavior change, based on SDL, and Sheth and Frazier (1982) attitude matrix, and suggests the need for perenniality of the social programs, based on the social change phases proposed by Andreasen (1994) and Prochaska and DiClemente (1983).